Psychedelic unselfing: self-transcendence and change of values in psychedelic experiences - Kähönen, Juuso (Frontiers in Psychology, 2023)
Psychedelic experiences can lead both to (re)connection to one’s values and changes in values, enhancing for example aesthetic appreciation, pro-environmental attitudes and prosocial behavior. I present an empirically informed framework of philosophical psychology to understand psychedelic value changes in relation to self-transcendence. Most of the empirically observed psychedelic value changes are toward the self-transcendent values of Schwartz’s value theory. As psychedelics also reliably cause various self-transcendent experiences (STEs), a parsimonious hypothesis is that STEs change values toward self-transcendent values. I argue that many of these value changes plausibly result from a form of self-transcendence called “unselfing”. Unselfing reduces egocentric attributions of salience and increases non-egocentric attention to the world, widening one’s perspective and shifting evaluation toward self-transcendent modes. I argue that values are inherently tied to various evaluative contexts and that unselfing can attune the individual to evaluative contexts, and accompanying values, beyond the self. Understood this way, psychedelics can, via self-transcendence, give temporarily enhanced access to self-transcendent values and function as sources of aspiration and value change. There are, however, multiple contextual factors complicating whether STEs lead to long-term changes in values. The framework is supported by various converging research strands establishing empirical and conceptual connections between a) long-term differences in egocentricity, b) STEs, and c) self-transcendent values. Similarly, the link between unselfing and value changes is supported by phenomenological and theoretical analysis of psychedelic experiences and by empirical findings on their long-term effects. This article furthers understanding of psychedelic value changes and contributes to discussions on whether value changes are justified, whether they result from cultural context, and whether psychedelics could function as tools of moral neuroenhancement.